Sunitinib uptake inhibits platelet function in cancer patients. (October 2016) - Sabrkhany, Siamack; Griffioen, Arjan W.; Pineda, Sharo; Sanders, Linda; Mattheij, Nadine; van Geffen, Johanna P.; Aarts, Maureen J.; Heemskerk, Johan W.M.; oude Egbrink, Mirjam G.A.; Kuijpers, Marijke J.E.
Abstract: Background: Sunitinib is an oral tyrosine kinase inhibitor used for cancer treatment. Patients treated with sunitinib are at higher bleeding risk. As tyrosine kinases are essential for platelet signalling, the effects of sunitinib on platelet function in vitro and in cancer patients on treatment were investigated. Patients and methods: Blood samples were collected from eight healthy volunteers and eight patients diagnosed with metastatic renal cell cancer (RCC) before and 2 weeks on treatment with sunitinib. Platelets from 15 additional healthy individuals were preincubated with sunitinib or vehicle to perform in vitro experiments. Immunofluorescence imaging, western blotting, light transmission aggregometry, whole blood perfusion over collagen, flow cytometry and ELISA were performed. Results: Confocal microscopy indicated that platelets sequester sunitinib in vitro and in patients. In platelets from healthy controls, tyrosine phosphorylation was inhibited by sunitinib. Also, sunitinib dose dependently reduced collagen- and ADP-induced aggregation, collagen-dependent thrombus formation and collagen-induced secretion of platelet-derived growth factor and β-thromboglobulin. In blood from RCC patients before treatment, thrombus formation and procoagulant activity under flow were 47% and 80% higher than in healthy controls. After 14 d of sunitinib treatment, platelet count was moderately, but significantly decreased (from 243 to 144 × 10 9 /l). At the same time, collagen-induced platelet aggregation as well as thrombus formation and phosphatidylserine exposure under flow were significantly reduced (by 45%, 16% and 61%, respectively). Conclusions: Sunitinib uptake by platelets inhibits collagen receptor-induced aggregation and thrombus formation via reduction of protein tyrosine phosphorylation and α-granule secretion. This dysfunction may contribute to the higher bleeding tendency observed in sunitinib-treated patients. Highlights: Sunitinib is sequestered by blood platelets in vitro and in patients on treatment. Sunitinib inhibits platelet activation, aggregation and thrombus formation. Sunitinib treatment moderately but significantly decreases platelet count. Together, this may contribute to the higher bleeding tendency observed during treatment. Clinicians need to be aware of the antiplatelet effects of sunitinib therapy.